The effect of an imagery training program on imagery ability, imagery use, and figure skating performance - Rogers, W.; Hall, C.; Buckholz, E. (Journal of Applied Sport Psychology, 1991)
Figure skaters (N = 29; mean age 13.7 yr) were divided into imagery only, verbal training, and a matched control group. Ss were assessed for imagery ability, imagery use, and free-skating performance before and after a 16 wk training program. Skaters trained in imagery use were more likely to use imagery before and after practice, to visualize skill elements more easily, and to see themselves winning more often. Their ability to "feel" themselves skate also improved more than in the verbal training and control groups. Skaters who became better at imagery also became more successful at completing their program elements, particularly the more difficult ones. Implication: Teaching imagery skills increases the use of imagery and is associated with performance improvements, particularly in difficult skill elements.